2018
DOI: 10.3892/mmr.2018.9277
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of promising molecular biomarkers and pathways for coronary artery disease using WGCNA and MetaDE methods

Abstract: The present study aimed to examine the molecular mechanisms of coronary artery disease (CAD). A total of four microarray datasets (training dataset no. GSE12288; validation dataset nos. GSE20680, GSE20681 and GSE42148) were downloaded from the Gene Expression Omnibus database, which included CAD and healthy samples. Weighted gene co-expression network analysis was applied to identify highly preserved modules across the four datasets. Differentially expressed genes (DEGs) with significant consistency in the fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Despite 1296 non-redundant genes that were differentially expressed, the final PPI network only had 228 genes, which means that the role of most genes in biofilm formation is still unknown. Using the key genes selected from the PPI network as references, the biofilm related genes in the strains were further mined through WGCNA [ 51 ]. WGCNA was performed to decompose 2032 coding genes into nine functional modules ( Figure 5 a).…”
Section: Discussionmentioning
confidence: 99%
“…Despite 1296 non-redundant genes that were differentially expressed, the final PPI network only had 228 genes, which means that the role of most genes in biofilm formation is still unknown. Using the key genes selected from the PPI network as references, the biofilm related genes in the strains were further mined through WGCNA [ 51 ]. WGCNA was performed to decompose 2032 coding genes into nine functional modules ( Figure 5 a).…”
Section: Discussionmentioning
confidence: 99%
“…downloaded the comprehensive database of gene expression of the sample population to analyze the correlation between genes and CVDs, the analysis of overlapping genes showed that Lck is one of the top three genes in a protein-protein interaction network. Nevertheless, related diagnostic techniques have not become popular without a large number of clinical trial data 86 . The accuracy, feasibility and effectiveness of using SFKs in the diagnosis of CVDs need more clinical trials to be tested.…”
Section: Sfks-related Possible Clinical Applicationmentioning
confidence: 99%
“…With the rapid development of high-throughput microarray technologies, the identification of genomic variations and biological mechanisms has improved our understanding of disease pathogenesis and treatment [ 16 , 17 ]. Weighted gene co-expression network analysis (WGCNA) is widely used to analyze gene expression microarray data, identify functional gene modules, and discover relationships between gene modules and disease traits [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%